Clinical profile and outcome of children with acute bacterial meningitis in a tertiary care centre in eastern Nepal - Bhatta, Mukesh; Kafle, Shyam Prasad; Rai, Basant; Subedi, Rejeena (Journal of Kathmandu Medical College, 2021)
Background: Bacterial meningitis is a severe infection of the central nervous system with varied clinical presentations. It is associated with substantial mortality and morbidity. Objectives: The objective of this study was to assess the clinical profile, including the clinical features, laboratory and radiological parameters, clinical course, treatment, response to treatment, complications, and outcome of children at discharge. Methods: A prospective observational study was conducted among 52 inpatient children of acute bacterial meningitis aged one month to 14 years over a period of six months. The patients were enrolled during admission and followed up daily till discharge. Socio-demographic, clinical, and diagnostic details and outcomes were recorded and analysed using statistical package for social sciences version 20. Results: The median age of the patients was two years with male to female ratio of 2:1. Fever (45, 87%), vomiting (37, 71%), seizure (33, 64%) and headache (22, 46%) were the most common symptoms. The cerebrospinal fluid culture was positive in three (6%) cases. Complications were seen in 20 (39%) patients including four (7.7%) deaths. Patients with prolonged fever, malnutrition, loss of consciousness, ear discharge, presence of meningeal signs, abnormal pupil, high cerebrospinal fluid protein, positive cerebrospinal fluid, and blood culture, low blood pH, and hyperlactataemia were significantly associated with complications (p <0.05). Conclusion: Factors like malnutrition, longer duration of fever, and abnormal neurological and laboratory findings were associated with higher rates of complications.